2022
DOI: 10.3390/cancers14194596
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RKIP in the Regulation of EMT in the Tumor Microenvironment

Abstract: The Raf Kinase Inhibitor Protein (RKIP) is a unique gene product that directly inhibits the Raf/Mek/Erk and NF-kB pathways in cancer cells and resulting in the inhibition of cell proliferation, viability, EMT, and metastasis. Additionally, RKIP is involved in the regulation of cancer cell resistance to both chemotherapy and immunotherapy. The low expression of RKIP expression in many cancer types is responsible, in part, for the pathogenesis of cancer and its multiple properties. The inhibition of EMT and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 187 publications
(282 reference statements)
1
10
0
Order By: Relevance
“…The levels of expression and activity of RKIP suggested that specific inhibition of ERK elevates the expression and activity of RKIP, which again suggests a possible feedback mechanism. This is in parallel to many recent evidences, which shows RKIP as a negative regulator of ERK (Cessna et al, 2022;Tang et al, 2010) .Specific inhibition of ERK by siRNA does not alter the expression and activity of MEK1/2 showing that targeted ERK modulation may result in better treatment of melanoma. The decreased levels of cFOS indicated that transcription regulation downstream of ERK might be through cFOS.…”
Section: Table 3: Values Of Parameters With Control Group With Respec...supporting
confidence: 86%
“…The levels of expression and activity of RKIP suggested that specific inhibition of ERK elevates the expression and activity of RKIP, which again suggests a possible feedback mechanism. This is in parallel to many recent evidences, which shows RKIP as a negative regulator of ERK (Cessna et al, 2022;Tang et al, 2010) .Specific inhibition of ERK by siRNA does not alter the expression and activity of MEK1/2 showing that targeted ERK modulation may result in better treatment of melanoma. The decreased levels of cFOS indicated that transcription regulation downstream of ERK might be through cFOS.…”
Section: Table 3: Values Of Parameters With Control Group With Respec...supporting
confidence: 86%
“…We observed the team strength of the wild-type (WT) network to be much greater than that of all 1000 randomly generated networks (figure 3 d ). This observation suggests that the organization of these molecular players into ‘teams’ in this network is not a coincidence, but rather a unique topological signature that can possibly facilitate specific couplings between cellular behaviour, such as the association of EMT with stemness and tamoxifen resistance [50,51] and opposite roles of RKIP and BACH1 in EMT [46,52].…”
Section: Resultsmentioning
confidence: 99%
“…As known, E-cadherin, N-cadherin, vimentin, and Snail are the markers of EMT ( Cessna et al, 2022 ). Tong et al (2017) mimicked the IRFA through thermal treatment under hypoxic conditions and found that the protein levels of HIF-1α, N-cadherin, vimentin, Snail, and TGF-β1 following IRFA were significantly elevated, while the expression of E-cadherin was reduced in HCC cells.…”
Section: Hif-1α Facilitates the Progression Of Hcc By Promoting The W...mentioning
confidence: 99%